ANALISIS LOGAM-LOGAM PADA BATU APUNG DAN MODIFIKASINYA SERTA UJI ADSORPSINYA PADA LARUTAN ASAM ASETAT - ., Zukria; Mardjan, Mardjan; Musa, Weny J.A (Jurnal Sainstek, 2012)
The study aims to analyze metal pregnancy in pumice and the modification with test adsorbtion to acetic acid. sample are taken from gorontalo city and kab. buol. at first sample menggrinding use uphand, then refined with mortal up to pass by sieve 100 mesh. Smoothing of both pumice modified with soaking in solution of HCl 1 M, 1 M H2SO4 and HNO3 1 M, the next made into pellets, calcined at 6000C. the metal pregnancy determination (Cr, Ca, Mg, Mn, and Fe) with Atomic Absorption Spectroscopy (AAS), Si and Al with technique gravimetric, with test adsorpsi solution with titration technique.The analysis showed levels of Si in Gorontalo and Buol pumice increased with immersion HNO3, and the smallest Al content in Gorontalo and Buol pumice with HNO3 immersion. The levels of metals (Cr, Ca, Mg, Mn, and Fe) on Buol's pumice increased with HCl immersion, and levels of metals (Cr, Ca, Mg, Mn, and Fe) in Gorontalo's pumice decreased by HCl immersion. Characterization results showed the two samples of pumice adsorb both modified and unmodified for acetic acid is very good.